2016
DOI: 10.1002/marc.201600353
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Bisphosphonate–Bioactive‐Glass Interactions for the Development of Self‐Healing and Bioactive Composite Hydrogels

Abstract: Hydrogels are widely recognized as promising candidates for various biomedical applications, such as tissue engineering. Recently, extensive research efforts have been devoted to the improvement of the biological and mechanical performance of hydrogel systems by incorporation of functional groups and/or inorganic particles in their composition. Bisphosphonates are a class of drugs, commonly used for treatment of osteoporosis, which exhibit a strong binding affinity for hydroxyapatite. In this study, the bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 29 publications
(45 reference statements)
0
29
0
Order By: Relevance
“…45S5 BG (Bioglass) particles were used as the inorganic building blocks since this glass type is the most common type of BG due to its strong bioactivity and biodegradability . We functionalized the gelatin particles with calcium‐binding bisphosphonate groups not only for their capacity to bind to calcium‐containing BGs, but also due to their antiosteoporotic efficacy . We first used a colloidal probe atomic force microscopy (AFM) technique to quantify the effect of the bisphosphonate functionalization of gelatin particles on the interparticle adhesion forces between gelatin and BG particles.…”
Section: Introductionmentioning
confidence: 99%
“…45S5 BG (Bioglass) particles were used as the inorganic building blocks since this glass type is the most common type of BG due to its strong bioactivity and biodegradability . We functionalized the gelatin particles with calcium‐binding bisphosphonate groups not only for their capacity to bind to calcium‐containing BGs, but also due to their antiosteoporotic efficacy . We first used a colloidal probe atomic force microscopy (AFM) technique to quantify the effect of the bisphosphonate functionalization of gelatin particles on the interparticle adhesion forces between gelatin and BG particles.…”
Section: Introductionmentioning
confidence: 99%
“…Important parameters which determine the properties of these hydrogels are the binding affinity between particles and polymer chains, the size of particles, the persistence length of polymers, the polymer concentration, and the crosslinking density of the gel network, i.e., the number of particles per gel volume. So far, hydrophobic, electrostatic, coordination interactions as well as molecular recognition motifs have been exploited to prepare this class of self‐healing biomaterials.…”
Section: Intrinsic Self‐healing Biomaterialsmentioning
confidence: 99%
“…Recent studies have shown that bisphosphonate functionalization of hyaluronic acid renders this polymer highly adhesive to calcium phosphate,[101b] calcium silicates,[101a] and magnesium silicate[101c] particles. Consequently, by exploiting these strong yet reversible coordination bonds between polymers and particles, injectable and self‐healing composite hydrogels have been synthesized which display promising results with respect to bone regeneration[101a,b] and drug delivery[101c] applications. In general, bisphosphonates exhibit a strong binding affinity for the mineral inorganic phase of bone, i.e., hydroxyapatite .…”
Section: Intrinsic Self‐healing Biomaterialsmentioning
confidence: 99%
See 2 more Smart Citations